Participation in the Archive of Open Source Software: An Interdisciplinary Literature Review. - Frluckaj, Hana; Acker, Amelia; Smith, Angela D. R.; Howison, James (Information & Culture, 2026)
In recent years, concerns have increased over the lack of contributor diversity in open source software (OSS), despite its status as a paragon of open collaboration. This article highlights the benefits and barriers presented by the openness of OSS participation, particularly among contributors from marginalized backgrounds. To deepen our understanding of how the information infrastructure of OSS perpetuates hegemonic injustices, we present an interdisciplinary literature review in three areas: open source culture and code-centrism, the dynamics of recordkeeping from archival studies, and nonparticipation in the digital realm from media studies. In bridging these literatures, we may theorize avenues of resistance for marginalized OSS contributors and transfer scholarly insights to help information scholars recognize power imbalances within information infrastructure.